Protective effect of hydroxytyrosol against oxidative stress in kidney cells - Incani, A.; Deiana, M.; Corona, G.; Atzeri, A.; Loru, D.; Rosa, A.; Melis, M.P.; Cabras, A.; Dessì, M. A. (Progress in Nutrition, 2007)
Bioavailability studies in animals and humans feeded with extravirgin olive oil have demonstrated that hydroxytyrosol, the major simple phenolic compound present in extravirgin olive oil, is dose-dependently absorbed and excreted. Once absorbed, it undergoes an extensive metabolism and both hydroxytyrosol and metabolites are present in high amount in the kidney, where they may exert an antioxidant action. A dietary intake of antioxidants has an important role in the prevention of oxidative stress induced renal dysfunction. In this study we monitored the ability of hydroxytyrosol to protect renal cells (LLC-PK1) following oxidative damage induced by H2O2. Oxidative stress was evaluated by monitoring the changes of the membrane lipid fraction. Hydroxytyrosol exerted a significant antioxidant action, inhibiting the production of fatty acids hydroperoxides and 7-ketocholesterol, major oxidation products of unsaturated fatty acids and cholesterol, and protecting the cells against H2O2-induced death.